On the formation of a legal framework for ensuring radiation safety (historical aspects) (Journal of actual problems of jurisprudence, 2021)
The article is devoted to the legal aspects of ensuring radiation safety. Kazakhstan is a unique country in the world, on the territory of which more than 650 atomic and hydrogen bombs have been tested. On its territory are polygons, where rocket tests continue, the fragments of which are radioactive. Also on its entire territory there are sites with natural and technogenic manifestations of increased radioactivity – deposits, exploration, industrial workings, etc., which contributes to the manifestations of high activity of uranium, radon. According to researchers, 30% of the territory of Kazakhstan has a potential for increased radon emissions. Therefore, radiation safety for Kazakhstan is a serious problem that must be addressed in various ways. One of the ways to solve this problem are legal means and methods. Therefore, the issue of protecting the population from radiation for Kazakhstan is vitally important, the concept of population and environment security for Kazakhstan acquires crucial importance and requires constant monitoring, analysis of existing problems in ensuring radiation safety, and improving this area of activity, taking into account world experience. The current system of radiation protection according to the International Commission on Radiation Protection (ICRP) should be considered as a set of legal, organizational, engineering, sanitary, hygienic, preventive, educational, general educational and information measures. The purpose of this article is to analyze the historical and theoretical grounds for the formation of the radiation safety system and the main trends in the evolution of the world experience in ensuring radiation safety; to understand the main conceptual approaches in the establishment of the International Organizations for the Management of Radiation Safety and Norm-setting when regulating radiation exposure; to give a picture of the evolution of the legal norms of radiation safety in the Soviet period and under independent Kazakhstan, to characterize the modern legal basis for radiation protection of man and the environment in Kazakhstan. The methodology of the study is determined by the nature and interrelation of the object and the subject, as well as the goals and tasks set, and includes the principles of historical and systemic approaches to the analysis of the processes and phenomena under study. The article also used a set of general scientific methods of research used in theoretical studies and includes analysis, synthesis, induction and deduction, system analysis and formalization, an analogy. Scientific and methodological basis was determined by legislative acts of International organizations, the former USSR, the Republic of Kazakhstan, reference materials, monographs, articles and other works by well-known scientists, containing descriptions of individual studies on the problems of ensuring radiation safety of mankind and the biosphere, including its legal aspects. As a result of the research, the evolution of theoretical and methodological approaches to the normalization of the radiation factor on the basis of knowledge of biological effects associated with the effects of radiation on the body, the establishment of the main legislative framework in the use of atomic energy in the Republic of Kazakhstan is shown; concerning natural sources of radiation on the basis of the world concept on legal regulation of radiation safety issues; the current system of normative legal acts regulating the protection of the population from radiation is shown. Key words: radiation, radiation doses, uranium, radon, antiradon protection, radiation monitoring, radiation protection, nuclear and radiation safety, laws, by-laws, international organizations, International Commission on Radiation Protection.